2019
DOI: 10.3389/fpsyg.2019.01394
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Self-Regulatory Management of Chronic Pain Through Dohsa-hou: Single-Case Series of Low-Functioning Hemodialysis Patients

Abstract: Hemodialysis patients suffer from long-term pain that drains their energy and contributes to behavioral interference and other negative effects on their daily lives that result in or exacerbate functional limitations. In addition, they deal with dietary restrictions, symptoms such as itching, lack of energy, and psychological stressors like the loss of self-concept and self-esteem. Self-regulation involves the capacity to notice, inform, and modulate responses and behavior, and research indicates that it promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Such incompliance can be attributed to the different sources of stress associated with hemodialysis, including hemodialysis complications, time-consuming treatment schedules, restriction of dietary and fluid intake, and prescription of multiple medications [ 3 , 4 ]. These sources of stress, in addition to the signs and symptoms of ESRD, result in diminished health-related quality of life, which is associated with increased risks of morbidity, mortality, and incompliance with hemodialysis therapy [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such incompliance can be attributed to the different sources of stress associated with hemodialysis, including hemodialysis complications, time-consuming treatment schedules, restriction of dietary and fluid intake, and prescription of multiple medications [ 3 , 4 ]. These sources of stress, in addition to the signs and symptoms of ESRD, result in diminished health-related quality of life, which is associated with increased risks of morbidity, mortality, and incompliance with hemodialysis therapy [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Dohsa-hou psychotherapy promotes self-regulatory management in hemodialysis patients. 28 Consequently, similar psycho-rehabilitative activities may greatly improve dietary adherence of peritoneal dialysis patients. In addition, self-control strongly predicts the likelihood of dietary adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in the step 3 movement task phase, participants were given the chance to physically experience the body awareness and mood regulatory effects from relaxation as a means to attenuate self-control as an advantage. Third, the procedural fidelity and long-term applicability of the movement tasks used in this stress management education program were established in a sample of hospital nurses who were not specialized in mental health care but were able to gain demonstrable skills in the domain over a short period under the guidance of mental health care specialist and qualified supervisor of the technique 13) . In this manner, this program has offered indications of feasibility and effectiveness motivating implementation.…”
Section: The Protocol Of the Stress Management Education Programmentioning
confidence: 99%